Imaging of the Axon Initial Segment. Issue 1 (2nd July 2019) - Di Re, Jessica; Kayasandik, Cihan; Botello‐Lins, Gonzalo; Labate, Demetrio; Laezza, Fernanda
Abstract: The axon initial segment (AIS) is the first 20‐ to 60‐μm segment of the axon proximal to the soma of a neuron. This highly specialized subcellular domain is the initiation site of the action potential and contains a high concentration of voltage‐gated ion channels held in place by a complex nexus of scaffolding and regulatory proteins that ensure proper electrical activity of the neuron. Studies have shown that dysfunction of many AIS channels and scaffolding proteins occurs in a variety of neuropsychiatric and neurodegenerative diseases, raising the need to develop accurate methods for visualization and quantification of the AIS and its protein content in models of normal and disease conditions. In this article, we describe methods for immunolabeling AIS proteins in cultured neurons and brain slices as well as methods for quantifying protein expression and pattern distribution using fluorescent labeling of these proteins. © 2019 by John Wiley & Sons, Inc.